Anthropogenic aerosol impacts on Pacific Coast precipitation in CMIP6 models. (12th July 2022) - Allen, Robert J; Zhao, Xueying
Abstract: Studies show anthropogenic aerosols (AAs) can perturb regional precipitation, including the tropical rain belt and monsoons of the Northern Hemisphere (NH). In the NH mid-latitudes, however, the impact of AAs on regional climate and precipitation remains uncertain. This work investigates the influence of AAs on wintertime precipitation along the North American Pacific Coast using models from the Coupled Model Intercomparison Project phase 6 (CMIP6). Over the early to mid-20th century, when U.S. and European AA and precursor gas emissions rapidly increased, a robust wintertime precipitation dipole pattern exists in CMIP6 all-forcing and AA-only forcing simulations, with wetting of the southern Pacific Coast (southward of ∼40 ∘  N) and drying to the north. A corresponding dynamical dipole pattern also occurs—including strengthening of the east Pacific jet southward of ∼40 ∘  N and weakening to the north—which is related to a Rossby wave teleconnection that emanates out of the tropical Pacific. Over the 21st century, when AAs are projected to decrease, an opposite hydro-dynamic dipole pattern occurs, including drying southward of 40 ∘  N (including California) and wetting to the north. Although Pacific Coast precipitation is dominated by natural variability, good multi-model agreement in the forced component of Pacific Coast precipitation change exists, with the AA pattern (north south dipole) dominating the greenhouse gas (uniform) pattern in the historical all-forcing simulations. A high level of agreement in individual model-realization trends also exists, particularly for the early part of the 20th century, suggesting a robustness to the human signature on Pacific Coast precipitation changes. Thus, historical precipitation responses along the Pacific Coast are likely to have been driven by a mixture of natural variability and forced changes. Natural variations appear to drive a large fraction of this change, but human influences (i.e. aerosols) are likely to have preconditioned the variability of the climate in this region.